Method for producing niobium oxide nanoparticles and use thereof
The method of heating a precursor solution with a niobium complex, reducing agent, and halogen additive at 140° C or higher effectively produces niobium oxide nanoparticles with particle sizes less than 10 nm, addressing production challenges and enhancing luminescent properties.
Patent Information
- Application Number
- JP2021124602
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-03
- Filing Date
- 2021-07-29
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2041-07-29
Smart Images

Figure 0007669035000001 
Figure 0007669035000002 
Figure 0007669035000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing niobium oxide nanoparticles and uses thereof. [Background technology]
[0002] In recent years, the application of nanoparticles such as quantum dots to light-emitting materials has raised hopes for the creation of unprecedented new light-emitting materials (for example, phosphors, electroluminescent (EL) materials, and semiconductor lasers).
[0003] At the nanoscale, where the particle diameter is 1 to 10 nm and the nanoparticles consist of about 10 to 50 nanoparticles, the band gap can be adjusted by the crystal size of the nanoparticles, so that it is possible to obtain characteristic luminescence properties that depend not only on the material and composition but also on the particle diameter.
[0004] In other words, the above-mentioned nanoparticles exhibit an electronic state that differs from the band structure based on the inherent crystal structure in a normal bulk state, and electrons (excitons) are confined in a three-dimensionally discretized state, i.e., they become quantum dots.
[0005] Previously developed quantum dot core materials were made from compounds containing cadmium metal, a toxic substance. Therefore, with a view to applying the devices to mass-produced consumer electronics, there was a need to develop non-toxic quantum dots or nanoparticles that do not contain harmful metals.
[0006] Niobium is mainly used as a raw material for nanoparticles that has low toxicity and is easily available. For example, Non-Patent Document 1 discloses that niobium pentoxide can have electrochemical properties by forming it into carbon nanotubes.
[0007] Also, Non-Patent Document 2 discloses a method for synthesizing nanoparticles by agglomerating niobium ethoxide in ethylene glycol. Furthermore, Non-Patent Document 3 discloses a method for synthesizing nanoparticles by dissolving niobium pentachloride in ethanol, gently neutralizing it, and agglomerating it over a long period of time. [Prior art documents] [Non-patent literature]
[0008] [Non-Patent Document 1] Vicentini, R.; Nunes, W.; Freitas, BGA; Silva, LMD; Soares, DM; Cesar, R.; Rodella, CB; Zanin, H.; Energy Stor. Mater., 2019, 22, 311. [Non-Patent Document 2] Tamai, K.; Hosokawa, S.; Teramura, K.; Shishido, T.; Tanaka, T.; Appl. Catal. B, 2016, 182, 469. [Non-Patent Document 3] Uekawa, N.; Kudo, T.; Mori, F.; Wu, YJ; Kakegawa, K.; J. Colloid Interface Sci., 2003, 264, 378. Summary of the Invention [Problem to be solved by the invention]
[0009] However, Non-Patent Document 1 does not disclose the production of niobium oxide nanoparticles having a particle diameter of less than 10 nm (single nano size). In addition, the size of the niobium oxide nanoparticles synthesized by the method described in Non-Patent Document 2 is about 50 to 200 nm, and single nano size niobium oxide nanoparticles cannot be produced. Furthermore, the method described in Non-Patent Document 3 requires multiple steps and takes a long time for synthesis.
[0010] As described above, with the above-mentioned techniques for producing nanoparticles using niobium as a raw material, it was difficult to control the particle size, and it was particularly difficult to efficiently produce nanoparticles with a particle size of less than 10 nm (single nano size).
[0011] In addition, while it is relatively easy to produce quantum dots from late transition metals such as gold and palladium, the problem is that late transition metals are expensive. Therefore, it would be highly desirable to be able to easily produce single nano-sized particles of niobium, an early transition metal and inexpensive material. [Means for solving the problem]
[0012] In order to solve the above problems, the present inventors conducted extensive research and found that niobium oxide nanoparticles having a particle size of less than 10 nm and novel luminescence properties can be produced by heating a precursor solution containing a niobium complex, a reducing agent as a solvent, and an additive having a halogen at 140° C. or higher, and thus completed the present invention. That is, the present invention includes the following features.
[0013] <1> The following steps (A) to (C): (A) dissolving a niobium complex in a reducing agent as a solvent to produce a precursor solution; (B) adding a halogen-containing additive to the precursor solution; (C) heating the precursor solution to which the additive has been added at 140° C. or higher.
[0014] <2> The niobium complex is one or more complexes selected from the group consisting of niobium oxalate, niobium acetate, niobium acetylacetonate, niobium pentachloride, niobium pentabromide, niobium pentaethoxide, and salts thereof. <1> The manufacturing method described in
[0015] <3> The reducing agent is one or more selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, and N-vinylformamide; <2> The manufacturing method described in
[0016] <4> The concentration of the niobium complex in the precursor solution is 0.01 M or more. <1> ~ <3> 13. The method for producing a semiconductor device according to any one of the preceding claims.
[0017] <5> The additive is at least one selected from the group consisting of trimethylsilyl chloride, hydrochloric acid, and dimethyldichlorosilane; <1> ~ <4> 13. The method for producing a semiconductor device according to any one of the preceding claims.
[0018] <6> In the step (B), a molar ratio of niobium in the precursor solution to the halogen contained in the additive is more than 1:1 and is 1:10 or less. <1> ~ <5> 13. The method for producing a semiconductor device according to any one of the preceding claims.
[0019] <7> Infrared spectroscopy revealed that the peak at 1600-1750 cm -1 Niobium oxide nanoparticles in which a peak indicating C=O stretching vibration is detected, halogen atoms are confirmed by energy dispersive X-ray analysis, and the average particle size measured by dynamic light scattering is less than 10 nm.
[0020] <8> 8. The niobium oxide nanoparticles according to claim 7, wherein the halogen atom is fluorine, chlorine, bromine, or iodine.
[0021] <9> The niobium molecule is protected by a molecule used as a reducing agent. <7> The niobium oxide nanoparticles according to claim 1.
[0022] <10> <7> ~ <9> A luminescent material containing the niobium oxide nanoparticles according to any one of claims 1 to 5.
[0023] <11> the light-emitting material is an electroluminescent material; <10> The light-emitting material according to claim 1.
[0024] <12> <10> or <11> A light-emitting element comprising the light-emitting material according to claim 1.
[0025] <13> The light-emitting element is an EL light-emitting element. <12> The light-emitting element according to claim 1. Effect of the Invention
[0026] According to one aspect of the present invention, niobium oxide nanoparticles having a particle size of less than 10 nm, which have been difficult to produce up until now, can be easily produced. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a schematic diagram showing the structure of niobium oxide nanoparticles according to one embodiment of the present invention. [Diagram 2] 1 is a graph showing the results of XPS measurement of the niobium oxide nanoparticles produced in the examples. [Diagram 3] FIG. 2 is a diagram showing the measurement results of the particle size distribution of niobium oxide nanoparticles produced in the examples. [Figure 4] 1 is a graph showing the results of fluorescence measurement of niobium oxide nanoparticles produced in the examples, and an image showing the luminescence behavior under black light. [Diagram 5] 1 is a graph showing the results of fluorescence measurement of niobium oxide nanoparticles produced in the examples. [Figure 6] 1 is a graph showing the results of fluorescence measurement of niobium oxide nanoparticles produced in the examples, and an image showing the luminescence behavior under black light. [Figure 7] 1 is a graph showing the results of measuring the absorbance of a niobium oxide nanoparticle solution produced in an example by UV-vis. [Figure 8] 1 is a graph of the fluorescence emission spectrum of niobium oxide nanoparticles produced in the examples. [Figure 9] 1 is a graph of the fluorescence excitation spectrum of niobium oxide nanoparticles produced in the examples. [Figure 10]1 is a graph showing the results of measuring the fluorescence lifetime of niobium oxide nanoparticles prepared using TMSCl as an additive in an example. [Figure 11] 1 is a graph showing the results of measuring the fluorescence lifetime of niobium oxide nanoparticles prepared using HCl as an additive in an example. [Figure 12] 1 is a graph showing the results of measuring the fluorescence lifetime of niobium oxide nanoparticles prepared without using any additive in an example. [Figure 13] 1 is a graph showing the results of IR measurement of niobium oxide nanoparticles produced in the examples. [Figure 14] FIG. 2 shows the results of STEM observation of niobium oxide nanoparticles prepared using TMSCl as an additive in the examples. [Figure 15] FIG. 2 shows the results of STEM observation of niobium oxide nanoparticles prepared using HCl as an additive in the examples. [Figure 16] FIG. 2 shows the results of STEM observation of niobium oxide nanoparticles prepared without using any additive in the examples. [Figure 17] FIG. 2 is a schematic diagram of an EL light-emitting device produced using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 18] FIG. 2 shows the results of a light emission test of an EL light emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 19] FIG. 2 shows the results of a light emission test of another EL light emitting device fabricated using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 20] 1 is a graph showing the results of measuring the emission spectrum of an EL light-emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 21] 1 is a graph showing the results of measuring the emission spectrum of another EL light-emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 22]1 is a graph showing the results of measuring the emission spectrum of still another EL light-emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention. [Diagram 23] 1 is a graph showing the results of measuring the emission spectrum of still another EL light-emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention. [Figure 24] 1 is a graph showing the results of measuring the current-voltage characteristics of an EL light-emitting device manufactured using niobium oxide nanoparticles according to one embodiment of the present invention and a p-type Si substrate. [Diagram 25] 10 is a graph showing the results of measuring the current-voltage characteristics of another EL light-emitting device manufactured using niobium oxide nanoparticles according to an embodiment of the present invention and a p-type Si substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] 1. Overview of the Invention A method for producing niobium oxide nanoparticles according to one embodiment of the present invention includes the following steps (A) to (C): (A) dissolving a niobium complex in a reducing agent as a solvent to produce a precursor solution, (B) adding a halogen-containing additive to the precursor solution, and (C) heating the precursor solution with the additive added at 140° C. or higher.
[0029] As the particle size of nanoparticles increases, the excitation energy is more likely to transition to a transition state, decreasing the probability of emission. Therefore, it is preferable for the particle size to be small. In particular, when the particle size is less than 10 nm, the degree of freedom of electron movement is extremely restricted, and the kinetic energy of the electrons increases. This increases the range of excitation and fluorescence wavelengths, resulting in a variety of emission characteristics.
[0030] However, as described above, it has been difficult to produce single-nanosized nanoparticles of niobium with the conventional techniques. Furthermore, the conventional techniques may require an inert gas atmosphere or the like for production, and there is room for improvement in terms of production costs.
[0031] In response to this, the present inventors have found that by using a reducing agent as the solvent for the precursor solution and adding an additive having a halogen to the solution, niobium oxide nanoparticles having an average particle size of less than 10 nm can be produced even when niobium is used as the raw material. The present inventors have also found that the above niobium oxide nanoparticles can be produced by a very simple method of heating in a solvent that is a reducing agent. Furthermore, the present inventors have found that it is possible to produce niobium oxide nanoparticles that are stable in water or in the air and are also thermally stable, and do not require an external protective agent to prevent aggregation.
[0032] Therefore, according to the present invention, it is possible to stably and easily produce niobium oxide nanoparticles having an average particle size of less than 10 nm.
[0033] In this specification, the term "single nano-sized nanoparticles" refers to nanoparticles having an average particle size of less than 10 nm. In addition, in this specification, the term "single nano-sized nanoparticles" refers not only to single nano-sized nanoparticles themselves, but also to quantum dots.
[0034] 2. Method for Producing Niobium Oxide Nanoparticles A method for producing niobium oxide nanoparticles according to one embodiment of the present invention is a method including the following steps (A) to (C). Step (A) dissolving a niobium complex in a reducing agent as a solvent to prepare a precursor solution Step (B) adding a halogen-containing additive to the precursor solution. Step (C) of heating the precursor solution containing the additive at 140° C. or higher <Process (A)> In step (A) of the present production method, a precursor solution is produced by dissolving a niobium complex in a reducing agent as a solvent. Step (A) can be carried out, for example, by mixing a niobium complex with a reducing agent as a solvent and dissolving the niobium complex in the reducing agent.
[0035] Since the niobium oxide nanoparticles produced in step (A) contain a reducing agent therein, the reducing agent can function as a protective agent for the niobium oxide nanoparticles, which is preferable for producing single-nanosized niobium oxide nanoparticles.
[0036] In one embodiment of the present invention, the niobium complex may be of one type or of two or more types.
[0037] The niobium oxide nanoparticles preferably have niobium whose surface valence measured by XPS described below is 4 and / or 5. From the viewpoint of luminescence properties, the valence is more preferably 4.
[0038] Specific examples of niobium complexes include niobium oxalate, niobium acetate, niobium acetylacetonate, niobium pentachloride, niobium pentabromide, niobium pentaethoxide, and salts thereof. Examples of salts include ammonium salts, potassium salts, magnesium salts, sodium salts, calcium salts, and the like. Among these, ammonium niobium oxalate is preferred from the viewpoints of low cost and easy availability in large quantities.
[0039] In one embodiment of the present invention, the niobium complex used may be a commercially available product, or may be one chemically synthesized by a known method.
[0040] By using the niobium complex, toxic metals such as cadmium are not used as raw materials for nanoparticles, and therefore non-toxic, single-sized nanoparticles can be produced.
[0041] The reducing agent used as a solvent for the precursor solution is not particularly limited as long as it is a reducing agent capable of dissolving the niobium complex. Only one type of reducing agent may be used, or two or more types may be mixed and used.
[0042] Examples of the reducing agent include N,N-dimethylformamide, N,N-dimethylacetamide, N-vinylformamide, N-methylformamide, N-methyl-2-pyrrolidone, etc. Among them, from the viewpoint of efficiently producing niobium oxide nanoparticles, N,N-dimethylformamide or N,N-dimethylacetamide is preferable.
[0043] The solvent of the precursor solution may further contain other solvents in addition to the reducing agent, so long as the solvent does not inhibit the function of the reducing agent as a protective agent, etc. Examples of the other solvents include N-methylformamide, N-methyl-2-pyrrolidone, tetrahydrofuran, etc. The smaller the content of the other solvent in the solvent, the more preferable, and it is most preferable that the solvent consists of the reducing agent.
[0044] The concentration of the niobium complex in the precursor solution is not particularly limited as long as it is a concentration that allows dissolution in the reducing agent. Specifically, the concentration is preferably 0.01 M or more, and more preferably 0.1 M or more.
[0045] <Process (B)> Step (B) is a step of adding a halogen-containing additive to the precursor solution. By adding the additive to the precursor solution, the particle size of the produced niobium oxide nanoparticles is less likely to vary, and niobium oxide nanoparticles having an average particle size of less than 10 nm can be stably produced.
[0046] The additive may be added alone or in combination of two or more kinds. The additive has a halogen. As described above, it is difficult to control the particle size of niobium to a single nano size. On the other hand, it has been revealed that the particle size of niobium oxide nanoparticles can be made to a single nano size by adding the additive in step (B).
[0047] In the examples described below, it has been confirmed that the surface valence of niobium oxide nanoparticles synthesized by adding the additive is changed from the corresponding valence of niobium oxide nanoparticles prepared without adding the additive.
[0048] From this result, it is considered that the halogen contained in the additive is coordinated to niobium instead of oxygen, thereby preventing the oxidation of the surface of niobium oxide nanoparticles. Although the detailed mechanism is unknown, it is speculated that the action of the additive in this way makes it possible to prepare single-nanosized niobium oxide nanoparticles.
[0049] From the viewpoint of further stabilizing the average particle size of the niobium oxide nanoparticles, the additive is preferably a compound having fluorine, bromine, iodine, or chlorine as a halogen.
[0050] Specific examples of the additive include trimethylsilyl chloride, trimethylsilyl bromide, hydrochloric acid, dimethyldichlorosilane, butyldimethylchlorosilane, etc. Among these, from the viewpoint of stabilizing the average particle size of the niobium oxide nanoparticles, trimethylsilyl chloride, trimethylsilyl bromide, or hydrochloric acid is preferable, and trimethylsilyl chloride or trimethylsilyl bromide is more preferable.
[0051] In the method for producing niobium oxide nanoparticles according to one embodiment of the present invention, in the step (B), the molar ratio of niobium in the precursor solution to the halogen contained in the additive is preferably 1:1 or more and 1:10 or less.
[0052] The above-mentioned structure is preferable from the viewpoint of increasing the luminous efficiency of the niobium oxide nanoparticles, and from this viewpoint, the above-mentioned molar ratio is more preferably 1:5 to 1:10.
[0053] The precursor solution may contain other components in addition to the precursor complex, solvent, and additives, as long as they do not inhibit the synthesis of niobium oxide nanoparticles. Examples of other components include triphenylphosphine, acetylacetone, and dibenzalacetone.
[0054] <Process (C)> Step (C) is a step of heating the precursor solution to which the additive has been added at 140° C. or higher.
[0055] The method of heating is not particularly limited, but it is preferable to use a conventionally known means such as a heater and to perform the heating while stirring. The temperature of the precursor solution in step (C) is 140°C or higher, more preferably 160°C or higher, and even more preferably 180°C or higher. If the heating temperature is 140°C or higher, it is considered that the halogen contained in the additive is easily coordinated to niobium, and the reducing agent is efficiently mixed with the niobium oxide nanoparticles. The upper limit of the heating temperature is not particularly limited, but may be 160°C or lower in reality. It is preferable that the heating temperature in step (C) is constant.
[0056] The heating time is not particularly limited, but is preferably 8 to 24 hours, more preferably 8 to 16 hours, and even more preferably 8 to 10 hours. If the heating time is 8 hours or more, niobium oxide nanoparticles can be stably produced. If the heating time is 24 hours or less, aggregation of nanoparticles is unlikely to occur.
[0057] The stirring in step (C) can be performed by a known stirring means such as a stirrer, a stirring rod, a stirring blade, etc. Alternatively, the stirring may be performed by shaking the container containing the precursor solution. The stirring speed may be appropriately selected after considering the preferable conditions.
[0058] From the viewpoint of efficiently heating the precursor solution, the step (C) may be performed after adding the precursor solution to a preheated solvent. The temperature, stirring speed, and time during preheating are not particularly limited, but the above-mentioned conditions can be appropriately selected.
[0059] After the heating is completed, the solution is preferably cooled to room temperature. Room temperature means 20 to 25° C. The cooling method is not particularly limited, and may be performed by a known method. Since the shape of the niobium oxide nanoparticles is easily stabilized by slow cooling, it is preferable to simply leave the solution at room temperature.
[0060] [3. Niobium oxide nanoparticles] The niobium oxide nanoparticles according to one embodiment of the present invention have a wavelength of 1600 to 1750 cm by infrared spectroscopy. -1 A peak showing C=O stretching vibration is detected in the niobium oxide nanoparticles, halogen atoms are confirmed by energy dispersive X-ray analysis, and the average particle size measured by dynamic light scattering is less than 10 nm. The niobium oxide nanoparticles can be produced by the method described above in [2. Production method of niobium oxide nanoparticles].
[0061] The average particle size of the niobium oxide nanoparticles according to one embodiment of the present invention is preferably 1 to 9 nm, more preferably 2 to 8 nm, and even more preferably 3 to 7 nm.
[0062] When the average particle size of the niobium oxide nanoparticles is less than 10 nm, the luminescence characteristics can be improved compared to niobium oxide nanoparticles that are not single nanosized, as shown in the examples described later. Furthermore, when the particle size of the nanoparticles is 1 nm or more, the luminescence characteristics are excellent.
[0063] The average particle size of the niobium oxide nanoparticles can be measured by dynamic light scattering by the method described in [Test 2: Measurement of particle size distribution by dynamic light scattering] below.
[0064] The niobium oxide nanoparticles are preferably protected by molecules that use niobium molecules as a reducing agent. The niobium oxide nanoparticles can be produced by the method described in [2. Method for producing niobium oxide nanoparticles] above, and therefore the niobium molecules of the niobium oxide nanoparticles may contain the reducing agent used as a solvent in [2. Method for producing niobium oxide nanoparticles] above.
[0065] It is believed that the niobium molecules of the niobium oxide nanoparticles are protected by the molecules of the reducing agent by containing the reducing agent inside the molecule. It is also believed that the niobium molecules in the niobium oxide nanoparticles are coordinated by the molecules of the reducing agent by containing the reducing agent inside the molecule. With the above-mentioned configuration, aggregation of the niobium oxide nanoparticles is unlikely to occur, and there is no need to add an external protective agent. In addition, the niobium oxide nanoparticles are more stable for a long time in water and in the air, and are also more thermally stable.
[0066] The niobium oxide nanoparticles may contain the additive inside the molecule, in addition to the reducing agent.
[0067] The presence of the reducing agent inside the molecules of the niobium oxide nanoparticles can be confirmed by observing a C═O stretching vibration peak derived from the reducing agent, such as an N,N-dimethylformamide molecule, using an IR method.
[0068] When the niobium oxide nanoparticles contain a reducing agent inside the molecule, the C=O stretching motion peak observed by infrared spectroscopy is in the range of 1600 to 1750 cm -1 and preferably 1600 to 1700 cm -1 , more preferably 1630 to 1680 cm -1The peak of the C=O stretching motion exhibited by the reducing agent can be confirmed, for example, by referring to the spectrum database published by the National Institute of Advanced Industrial Science and Technology. The infrared spectroscopic analysis can be performed, for example, by using an IR Affinity-1 FT-IR (manufactured by Shimadzu Corporation) device described in the examples below, by sandwiching a sample of niobium oxide nanoparticles between NaCl plates and measuring them.
[0069] 1 is a schematic diagram showing a state in which niobium molecules in niobium oxide nanoparticles are coordinated with molecules of a reducing agent. The niobium oxide nanoparticles according to one embodiment of the present invention have a peak intensity of 1600 to 1750 cm by infrared spectroscopy. -1 Since a peak of C=O stretching motion is detected in the range, it can be inferred that the niobium molecules in the niobium oxide nanoparticles are coordinated by the molecules of the reducing agent.
[0070] For example, when N,N-dimethylformamide molecules are contained as the reducing agent inside the niobium oxide nanoparticles, the peak of the C=O stretching motion is 1675 cm -1 When N,N-dimethylacetamide is used as the reducing agent, the peak is observed at 1646 cm -1 When N-vinylformamide is used as the reducing agent, the -1 When N-methylformamide is used as the reducing agent, the -1 When N-methyl-2-pyrrolidone is used as the reducing agent, the peak is observed at 1667 cm -1 is observed.
[0071] The excitation wavelength of the niobium oxide nanoparticles is not particularly limited, but is preferably 270 to 400 nm, more preferably 300 to 400 nm, and even more preferably 350 to 370 nm. When the excitation wavelength of the niobium oxide nanoparticles is in the above range, the fluorescence intensity is excellent.
[0072] The niobium oxide nanoparticles preferably have a fluorescent wavelength of 400 to 500 nm, more preferably 420 to 480 nm, and even more preferably 440 to 470 nm. When the niobium oxide nanoparticles have a fluorescent wavelength in the above range, the fluorescent intensity is excellent.
[0073] The fluorescence lifetime of the niobium oxide nanoparticles is preferably 100 nanoseconds or less, more preferably 50 nanoseconds or less, and even more preferably 30 nanoseconds or less. If the fluorescence lifetime is 100 nanoseconds or less, the afterglow time of the fluorescent emission is sufficiently short, which is preferable for application to a light-emitting device.
[0074] The niobium oxide nanoparticles preferably have two or more types of fluorescence lifetimes, which means that the niobium oxide nanoparticles have a plurality of fluorescence mechanisms, making the niobium oxide nanoparticles applicable to a wider range of devices.
[0075] In this specification, the fluorescence lifetime means the time from when the niobium oxide nanoparticles first emit light until the emission intensity becomes 37% of the emission intensity at the time of the first emission.
[0076] The niobium oxide nanoparticles contain the halogen added in the step (B). The presence of halogen atoms in the niobium oxide nanoparticles is shown by confirming the presence of halogen atoms by energy dispersive X-ray analysis. Examples of the halogen atoms include those described in [2. Method for producing niobium oxide nanoparticles] above.
[0077] The presence of halogen atoms can be confirmed by energy dispersive X-ray analysis, for example, by observing characteristic X-rays originating from halogen atoms using an EDS (energy dispersive X-ray analyzer) equipped with an atomic resolution analytical electron microscope (JEM-ARM200F, manufactured by JEOL Ltd.) described in the Examples below.
[0078] [4. Uses of niobium oxide nanoparticles] The niobium oxide nanoparticles according to one embodiment of the present invention can be used, for example, as a light-emitting material, a catalyst, an electronic material, a functional ceramic, etc. The preferred use is as a light-emitting material, and more preferably as an EL (electroluminescence) light-emitting material.
[0079] The light-emitting material or EL light-emitting material can be used as a light-emitting element, a phosphor application element, a wavelength conversion film, a dye laser, a bioluminescent marker, etc. The light-emitting element is preferable, and an EL light-emitting element is more preferable.
[0080] The light-emitting element or EL light-emitting element can be, for example, a semiconductor laser, a light-emitting diode, etc. Among them, from the viewpoint of the light-emitting material, a semiconductor laser is preferable.
[0081] The shape of the EL light emitting device using nanoparticles according to one embodiment of the present invention is not particularly limited, but may be, for example, the shape shown in FIG.
[0082] When a Si substrate is used in the manufacture of the EL device, the type of the Si substrate is not particularly limited. For example, the Si substrate may be a p-type or an n-type.
[0083] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0084] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.
[0085] [Method of manufacturing niobium oxide nanoparticles] (Niobium oxide nanoparticle solutions 1-3) First, 0.1 mmol (33.9 mg) of ammonium niobium oxalate (hereinafter, "ANO") (Companhia Brasileira de Metalurgia e. Mineracao, CBMM) was dissolved in 1 mL of N,N-dimethylformamide (hereinafter, "DMF") (purity: ≧99.7% (by gas chromatography), Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare a 0.1 M precursor solution (step (A)). ANO is a niobium complex, and DMF is a solvent that acts as a reducing agent when heated.
[0086] To the precursor solution, 0.065 mL (0.5 mmol) of trimethylsilyl chloride (hereinafter, "TMSCl", purity: >98.0% (by gas chromatography), manufactured by Tokyo Chemical Industry Co., Ltd.) or 0.05 mL (0.5 mmol) of 10 M HCl (prepared from approximately 12 M HCl manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added as an additive (step (B)). The obtained solutions were named additive-containing precursor solutions 1 and 2, respectively. As a control, a precursor solution without the addition of an additive (hereinafter, "additive-free precursor solution") was also prepared. The molar ratio of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:5.
[0087] Next, 50 mL of DMF was added to the three-neck flask, and the three-neck flask was placed in a mantle heater and preheated at 140° C. and 1500 rpm for 10 minutes.
[0088] Then, 0.5 mL of the additive-containing precursor solution 1 was added to the three-neck flask, and the solution was heated at 140° C. for 8 hours while stirring, and then allowed to stand until it reached room temperature, to obtain a solution 1 of niobium oxide nanoparticles with a concentration of 1 mM (step (C)). The same operation was performed on the additive-containing precursor solution 2 and the additive-free precursor solution, to obtain a niobium oxide nanoparticle solution 2 with a concentration of 1 mM and a niobium oxide nanoparticle solution 3 without additives, respectively.
[0089] (Niobium oxide nanoparticle solution 4) Niobium oxide nanoparticle solution 4 having a concentration of 1 mM was obtained in the same manner as in the above "(Niobium oxide nanoparticle solutions 1 to 3)" except that the amount of TMSCl added was 0.13 mL (1.0 mmol). The molar ratio (Nb:TMSCl) of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:10.
[0090] (Niobium oxide nanoparticle solution 5) 0.5 mmol (169.5 mg) of ANO was dissolved in 1 ml of DMF to prepare a 0.5 M precursor solution (step (A)). Niobium oxide nanoparticle solution 5 with a concentration of 5 mM was obtained in the same manner as in the above "(Niobium oxide nanoparticle solutions 1 to 3)" except that 0.325 ml (2.5 mmol) of TMSCl was added as an additive to the precursor solution (step (B)). The molar ratio (Nb:TMSCl) of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:5.
[0091] (Niobium oxide nanoparticle solution 6) Niobium oxide nanoparticle solution 6 having a concentration of 1 mM was obtained in the same manner as in the above "(Niobium oxide nanoparticle solutions 1 to 3)" except that the amount of TMSCl added was 0.013 mL (0.1 mmol). The molar ratio (Nb:TMSCl) of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:1.
[0092] (Niobium oxide nanoparticle solution 7) Niobium oxide nanoparticle solution 7 having a concentration of 1 mM was obtained in the same manner as in the above "(Niobium oxide nanoparticle solutions 1-3)" except that 0.065 mL (0.5 mmol) of trimethylsilyl bromide (hereinafter, "TMSBr") was added as an additive instead of TMSCl. The molar ratio (Nb:TMSCl) of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:5.
[0093] (Niobium oxide nanoparticle solution 8) A 0.1M precursor solution was prepared in the same manner as in the above "(Niobium oxide nanoparticle solutions 1-3)" except that 1 mL of N,N-dimethylacetamide (DMAc) was used instead of N,N-dimethylformamide and the preheating temperature was set to 160°C. Next, the precursor solution was subjected to the same operation as in the above "(Niobium oxide nanoparticle solutions 1-3)" when TMSCl was used as an additive, to obtain a niobium oxide nanoparticle solution 8 with a concentration of 1 mM. The molar ratio (Nb:TMSCl) of niobium in the precursor solution in step (B) to the halogen contained in the additive was 1:5.
[0094] In the figures below, "Nb NPs (without additive)" or "Nb NPs" indicates "niobium oxide nanoparticles prepared without adding any additives during production," "Nb NPs (TMSCl)" indicates "niobium oxide nanoparticles prepared with TMSCl added as an additive during production," and "Nb NPs (HCl)" indicates "niobium oxide nanoparticles prepared with HCl added as an additive during production."
[0095] In addition, "Nb NPs(TMSBr)" refers to "niobium oxide nanoparticles prepared by adding TMSBr as an additive during production," and "NB NPs(TMSCl)(DMAc)" refers to "niobium oxide nanoparticles prepared by using DMAc as a solvent during production."
[0096] [Test 1: Measurement of the electronic state of the constituent elements by X-ray photoelectron spectroscopy] To investigate the electronic state of niobium on the surface of niobium oxide nanoparticles, the valence of the surface of niobium oxide nanoparticles was measured by X-ray photoelectron spectroscopy (XPS). XPS measurements were performed using a ULVAC-PHI PHI5000 VersaProbe (ULVAC-PHI, Inc.).
[0097] The samples used in the measurement were prepared by the following method. First, the niobium oxide nanoparticle solution 1 and the niobium oxide nanoparticle solution 3 prepared in the above [Method for producing niobium oxide nanoparticles] were each concentrated using an evaporator. Free DMF was then completely removed by vacuum distillation. The resulting niobium oxide nanoparticles (hereinafter referred to as niobium oxide nanoparticles 1) and the particle paste of niobium oxide nanoparticles not containing additives (hereinafter referred to as niobium oxide nanoparticles 3) were stored in a state where argon was sealed.
[0098] Next, the particle paste of niobium oxide nanoparticles 1 and niobium oxide nanoparticles 3 was sandwiched between two silver plates (0.2 x 0.3 cm, thickness 0.2 mm) and pressed by finger pressure. Next, the two silver plates were separated, and the pressed particle paste was divided into two halves, and spread out into a flat shape. Thereafter, the particle paste was peeled off from the silver plate to obtain two pressed particle pastes, each of which was used as a sample. In addition, a normal niobium foil was used as a control. Both samples were placed on a sample stage, and the valence of the surface was measured using Alkα rays. The results are shown in Figure 2.
[0099] As shown in Figure 2, while the normal niobium foil showed spectra of 0 and 3 valences, among the niobium oxide nanoparticle samples, niobium oxide nanoparticles 3 (Nb NPs) to which no additive was added mostly showed spectra of 5 and 3 valences. Therefore, it is considered that most of the surface of niobium oxide nanoparticles 3 is in an oxidized state.
[0100] On the other hand, it was shown that the pentavalent peak of niobium oxide nanoparticles 1 with the additive was partially shifted to the tetravalent side. Therefore, it is considered that in niobium oxide nanoparticles 1, the chloro group of the additive is coordinated instead of oxygen, thereby suppressing surface oxidation. Therefore, it is expected that the additive changes not only the particle size of niobium oxide nanoparticles, but also the luminescence properties of the material itself.
[0101] [Test 2: Measurement of particle size distribution by dynamic light scattering method] The average particle size of the niobium oxide nanoparticles synthesized in the above [Method for producing niobium oxide nanoparticles] was measured by dynamic light scattering (DLS) using a Zetasizer nano ZSP (manufactured by Malvern) as the measuring device.
[0102] The samples used in the measurement were prepared by the following method. First, each of the niobium oxide nanoparticle solutions 1 to 3 was concentrated using an evaporator, and the concentrated solution was dispersed in DMF to obtain a sample. The holder temperature of the measuring device was set to 25.0°C, and the sample was placed in the measuring device, and the average particle size of the niobium oxide nanoparticles was calculated using a dynamic light scattering method.
[0103] The measuring device irradiates the sample with laser light and observes the scattered light of the niobium oxide nanoparticles in the sample, thereby observing the fluctuations in scattered light intensity due to the Brownian motion of the niobium oxide nanoparticles. Next, an autocorrelation function is obtained from the fluctuations by a photon correlation method, and the diffusion coefficient, average particle size, and particle size distribution of the niobium oxide nanoparticles are obtained by using a histogram analysis. FIG. 3 is a diagram showing the measurement results of the particle size distribution of niobium oxide nanoparticles. The upper part of FIG. 3 shows the measurement results of niobium oxide nanoparticles 3, the middle part shows the measurement results of niobium oxide nanoparticles 1, and the lower part shows the measurement results of niobium oxide nanoparticles 2.
[0104] 3 shows that the average particle size of niobium oxide nanoparticles 3 prepared without adding additives was 100 nm or more, whereas the average particle size of niobium oxide nanoparticles 1 and 2 prepared with the additives TMSCl and HCl was less than 10 nm. Therefore, it was shown that single-nanosized niobium oxide nanoparticles can be produced by adding additives.
[0105] [Test 3: Fluorescence measurement] Fluorescence measurements were performed to examine the wavelength at which the niobium oxide nanoparticles emit light. Fluorescence measurements were performed using RF-6000 (manufactured by SHIMADZU). For the measurements, the niobium oxide nanoparticle solutions 1 to 8 prepared in the above [Method of manufacturing niobium oxide nanoparticles] were used as is. The solutions with a concentration of 0.1 mM were prepared by diluting the niobium oxide nanoparticle solutions 1 to 8 by 10 times. Each sample was placed in a quartz cell and measured at room temperature. The niobium oxide nanoparticle solution 8 with a concentration of 10 mM was prepared by distilling off the DMF in the niobium oxide nanoparticle solution 8 with an evaporator, and then adding DMF again so that the concentration of the solution became 10 mM.
[0106] The measurement conditions were as follows: excitation wavelength 350 nm, measurement range 360 to 600 nm, data interval 1.0 nm, scan speed 2000 nm / min, spectral bandwidth 5.0 nm on both the excitation side and fluorescence side, and sensitivity Low.
[0107] The results are shown in Figures 4 to 6. The upper part of Figure 4 shows the measurement results for niobium oxide nanoparticle solution 3, the middle part shows the measurement results for niobium oxide nanoparticle solution 1, and the lower part shows the measurement results for niobium oxide nanoparticle solution 2.
[0108] The upper right panel of Fig. 4 shows the luminescence behavior of niobium oxide nanoparticle solution 3 with a concentration of 1 mM when irradiated with black light (wavelength 352 nm). The middle and lower right panels of Fig. 4 show the luminescence behavior of niobium oxide nanoparticle solutions 1 and 2 with concentrations of 0.1 mM when irradiated with the black light. The luminescence behavior was observed using a UV-BOX (KENIS), a portable dark box equipped with two types of UV light sources, long wave and short wave.
[0109] 5 shows the measurement results of niobium oxide nanoparticle solution 4, the middle shows the measurement results of niobium oxide nanoparticles 5, and the bottom shows the measurement results of niobium oxide nanoparticles 6.
[0110] In addition, the top left of Figure 6 shows the measurement results for niobium oxide nanoparticle solution 7, the top right shows the luminescence behavior of niobium oxide nanoparticle solution 7 at a concentration of 0.1 mM when irradiated with black light (wavelength 254 nm), the bottom left shows the measurement results for niobium oxide nanoparticle solution 8, and the bottom right shows the luminescence behavior of niobium oxide nanoparticle solution 8 at a concentration of 1 mM when irradiated with black light.
[0111] The observation of the luminescence behavior was carried out using a battery-powered UV lamp, MiniMAX UV Lamp UV-5NF (manufactured by SPECTROLINE).
[0112] Figures 4 and 6 show that niobium oxide nanoparticle solution 3, which was produced without any additives, emitted strong light at a concentration of 1.0 mM, whereas niobium oxide nanoparticle solutions 1, 2, and 7, which were prepared with additives, emitted strong light at a concentration of 0.1 mM. Additionally, niobium oxide nanoparticle solution 8, in which the solvent was changed, emitted strong light at a concentration of 1 mM.
[0113] In addition, it was found from FIG. 6 that both niobium oxide nanoparticle solutions 7 and 8 emit light when irradiated with black light.
[0114] [Test 4: Measurement of absorbance by UV-vis] To investigate the remaining precursors used in the production of niobium oxide nanoparticles, absorbance was measured by UV-vis (ultraviolet-visible spectroscopy). UV-vis was measured using a spectrophotometer V-770 (JASCO). For the measurements, 0.1 mM solutions obtained by diluting niobium oxide nanoparticle solutions 1 to 3 by a factor of 10 were used. Each sample was placed in a quartz cell and measurements were performed at room temperature. The results are shown in Figure 7. The top row of Figure 7 shows the measurement results for niobium oxide nanoparticle solution 3, the middle row shows the measurement results for niobium oxide nanoparticle solution 1, and the bottom row shows the measurement results for niobium oxide nanoparticle solution 2.
[0115] As shown in FIG. 7, none of the niobium oxide nanoparticle solutions showed a peak of ammonium niobium oxalate, which is the precursor, and therefore it was found that the precursor did not remain in the niobium oxide nanoparticles.
[0116] [Test 5: Measurement of photoluminescence and photoluminescence excitation] In order to evaluate the changes in the light emission process of niobium oxide nanoparticles, photoluminescence (PL) and photoluminescence excitation (PLE) were measured. In the PL measurement, the fluorescence emission spectrum was measured, and in the PLE measurement, the fluorescence excitation spectrum was measured. The PL measurement and the PLE measurement were performed using a spectrofluorometer F-2700 (manufactured by HITACHI). For the measurement, the niobium oxide nanoparticle solutions 1 to 3 prepared in the above [Method for producing niobium oxide nanoparticles] were used as they were. The solutions with a concentration of 0.1 mM were prepared by diluting each solution 10 times.
[0117] Each sample was placed in a quartz cell and measurements were performed at room temperature. The excitation wavelength during PL measurements was fixed at 350 nm, the fluorescence start wavelength was 360 nm, and the fluorescence end wavelength was 600 nm. The excitation start wavelength during PLE measurements was 220 nm, and the excitation end wavelength was 400 nm. The results are shown in Figures 8 and 9. The upper rows of Figures 8 and 9 show the measurement results for niobium oxide nanoparticle solution 3, the middle rows show the measurement results for niobium oxide nanoparticle solution 1, and the lower rows show the measurement results for niobium oxide nanoparticle solution 2, respectively.
[0118] FIG. 8 shows that, similarly to the fluorescence measurements shown in FIG. 4, niobium oxide nanoparticle solution 3 prepared without adding additives during production emitted strong light at a concentration of 1.0 mM, whereas niobium oxide nanoparticle solutions 1 and 2 prepared with additives emitted strong light at a concentration of 0.1 mM.
[0119] Furthermore, Figure 9 shows that, similar to the PL intensity, niobium oxide nanoparticle solution 3 prepared without adding any additives during production was strongly excited at a concentration of 1.0 mM, whereas niobium oxide nanoparticle solutions 1 and 2 prepared with the addition of additives were strongly excited at a concentration of 0.1 mM.
[0120] The difference in the results between niobium oxide nanoparticle solutions 1 and 2 and niobium oxide nanoparticle solution 3 is believed to be due to the fact that niobium oxide nanoparticles 1 and 2 have an average particle size of less than 10 nm due to the addition of additives during preparation.
[0121] [Test 6: Measurement of fluorescence lifetime] Fluorescence lifetime is the time it takes for an excited molecule to return to its ground state. The lifetime when all excited molecules emit fluorescence and return to the ground state is called the natural lifetime, but in reality, there is a certain probability that they will emit fluorescence due to non-radiative transitions (relaxation to a triplet state due to intersystem crossing, internal conversion to thermal energy, etc.). The probability of this transition occurring is called the quantum yield, and the fluorescence lifetime is calculated by multiplying the natural lifetime by the quantum yield.
[0122] The fluorescence lifetime of the niobium oxide nanoparticles was measured using an excitation pulse laser Ultra50 (Quantel) (excitation wavelength 266 nm), a spectrometer SP2358 (Princeton Instruments), and a photodetector PI-MAX4 (Princeton Instruments).
[0123] For the measurement, niobium oxide nanoparticle solutions 1 to 3 prepared in the above [Production method of niobium oxide nanoparticles] were used as they were. The 0.1 mM solution was prepared by diluting each solution 10 times. Each sample was placed in a quartz cell and measured at room temperature. In this test, the time when the emission intensity reached about 37% of the initial intensity was taken as the fluorescence lifetime. The measurement was performed by continuously measuring 300 3 nanosecond frames, and the measurement start time was shifted by 0.1 nanoseconds to obtain data on the fluorescence lifetime against time. The results are shown in Figures 10 to 12.
[0124] FIG. 10 shows the measurement results of niobium oxide nanoparticle solution 1. FIG. 11 shows the measurement results of niobium oxide nanoparticle solution 2. FIG. 12 shows the measurement results of niobium oxide nanoparticle solution 3. The left side of each figure shows the measurement results when the concentration of the niobium oxide nanoparticle solution is 0.1 mM and the measurement time is 30 nanoseconds, the center figure shows the measurement results when the concentration of the niobium oxide nanoparticle solution is 0.1 mM and the measurement time is 300 nanoseconds, and the right side shows the measurement results when the concentration of the niobium oxide nanoparticle solution is 1 mM and the measurement time is 30 nanoseconds. The horizontal axis of each figure represents the measurement time, and the vertical axis represents the normalized PL intensity. Fluorescence lifetime measurements were performed at a wavelength of 350 nm.
[0125] 10 to 12, the fluorescence lifetime of the niobium oxide nanoparticles was about several nanoseconds to several tens of nanoseconds. Therefore, it was shown that the light emitted by the niobium oxide nanoparticles was fluorescence due to the discrete energy levels formed in the niobium oxide nanoparticles, which is a characteristic of the niobium oxide nanoparticles, or due to the localized levels near the surface of the niobium oxide nanoparticles.
[0126] It is also found that increasing the concentration of the solution shortens the fluorescence lifetime of the niobium oxide nanoparticles due to energy transfer between the niobium oxide nanoparticles. Such fluorescence characteristics indicate that the fluorescence quantum efficiency of the niobium oxide nanoparticles is relatively high. Therefore, it was found that the niobium oxide nanoparticles according to one embodiment of the present invention have good properties as a luminescent material.
[0127] [Test 7: IR measurement] In order to analyze the components contained in the niobium oxide nanoparticles, IR (infrared spectroscopy) measurements were performed. The IR measurements were performed using an IRAffinity-1 FT-IR (manufactured by Shimadzu Corporation). The samples used in the measurements were prepared by the following method. First, the niobium oxide nanoparticle solutions 1 to 3 prepared in the above [Method of manufacturing niobium oxide nanoparticles] were concentrated using an evaporator. Furthermore, the niobium oxide nanoparticles were evaporated in a vacuum (10 -3 torr), and then each concentrated solution was pasted onto a NaCl plate and sandwiched between two NaCl plates to prepare samples.
[0128] The results are shown in Figure 13. The horizontal axis of Figure 13 is wave number (cm -1 ) In the figure, "Nb NPs (TMSCl)" indicates the result when niobium oxide nanoparticle solution 1 was applied, "Nb NPs (HCl)" indicates the result when niobium oxide nanoparticle solution 2 was applied, and "Nb NPs none" indicates the result when niobium oxide nanoparticle solution 3 was applied. "DMF" indicates the result when only DMF was applied.
[0129] Figure 13 shows that the peaks of all samples were similar to those of DMF, the solvent of the precursor solution, and therefore it was found that the niobium oxide nanoparticles produced were protected by the molecules of DMF used as a reducing agent.
[0130] [Test 8: Observation of niobium oxide nanoparticles using a scanning transmission electron microscope (STEM) and measurement of average particle size] Niobium oxide nanoparticles were observed by STEM using a JEM-ARM-200F (manufactured by JEOL Ltd.) as follows. Specifically, the niobium oxide nanoparticle solutions 1 to 3 prepared in the above [Method for producing niobium oxide nanoparticles] were concentrated using an evaporator, and the solution dispersed in ethanol was used as a sample. The sample was dropped onto a copper grid, and observation was performed at an accelerating voltage of 200 kV. The results are shown in Figures 14 to 16.
[0131] The left side of Figures 14 and 15 and the top left of Figure 16 show STEM images of niobium oxide nanoparticles. In the figures, the circled areas represent niobium oxide nanoparticles. The top right of each figure shows the particle size distribution of niobium oxide nanoparticles, measured by a method of calculating the particle size in the observation field in comparison with a scale bar. The average particle size was determined by calculating the number average from the obtained particle size distribution data (sample number 75 to 103). The bottom right of each figure shows the results of elemental analysis by energy dispersive X-ray (EDS) analysis.
[0132] As shown in Figures 14 and 15, niobium oxide nanoparticles 1 and 2 prepared using additives showed an average particle size of less than 10 nm. However, in niobium oxide nanoparticles 3, which were produced without the addition of additives, some particles with a particle size of about 100 nm were observed (lower left photograph in Figure 16). This shows that the generation of nanoparticles with a particle size of 10 nm or more can be suppressed by adding additives.
[0133] The average particle size of niobium oxide nanoparticles 3, which were produced without any additives, showed a different result from that of Test 2. This is because the measurement of the average particle size by STEM is a method based on local observation, whereas the measurement of the average particle size by dynamic light scattering is a method that measures the entire solution.
[0134] In the diagrams showing the results of the EDS analysis, NbLl and NbLa indicate energies derived from niobium, and ClKa and ClKb indicate energies derived from chlorine. The EDS analysis tables in Figures 14 to 16 show that niobium and chlorine are contained in each of the niobium oxide nanoparticles.
[0135] [Test 9: Preparation of EL light-emitting device] An EL light-emitting device was produced using the niobium oxide nanoparticle solution 1 produced in the above [Production method of niobium oxide nanoparticles]. A schematic diagram of the EL light-emitting device is shown in Figure 17. Specifically, first, an n-type Si substrate (resistivity 1-10 Ωcm) and a p-type Si substrate (resistivity 0.01-0.02 Ωcm) were cleaned with acetone and isopropyl alcohol.
[0136] Next, an Al electrode (40 nm thick) was deposited on the back side of the substrate using a vacuum heating deposition apparatus. After that, niobium oxide nanoparticle solution 1 ("Nb NP" in FIG. 17) prepared using TMSCl as an additive was drop-cast on the front side of the substrate and deposited by vacuum drying.
[0137] Further, a transparent electrode (ITO) (thickness 300 nm) was formed thereon by sputtering to obtain an EL light-emitting element. The EL light-emitting element was attached to a copper plate with a conductive paste to obtain an element for measuring current-voltage characteristics (IV characteristics) and EL spectrum. At this time, the Al electrode on the back surface of the substrate was in contact with the copper plate. A probe electrode was brought into contact with the copper plate and the ITO layer on the EL light-emitting element, and a voltage was applied to the EL light-emitting element at room temperature using a source measure unit GS820 (manufactured by Yokogawa Measurement Co., Ltd.) as a power source. The values of the applied voltage and the injected current were 9 V and 36 mA, respectively. The light-emitting state was observed with the naked eye. The results are shown in FIG. 18. In addition, in order to confirm that the results shown in FIG. 18 are reproducible, the observation results of the light-emitting elements A and B subjected to the same preparation method and the same measurement method as the light-emitting element shown in FIG. 18 are shown in FIG. 19. The applied voltage and injected current during observation depend on the size of the EL light-emitting elements A and B prepared for reproducibility confirmation, and were appropriately changed according to the size.
[0138] Figure 18 shows the test results of an EL light-emitting device prepared using a p-type Si substrate. Figure 18 shows that light was emitted when a p-type Si substrate was used. Therefore, it was found that the niobium oxide nanoparticles according to one embodiment of the present invention can emit light by themselves.
[0139] Fig. 19 shows the test results of EL light-emitting elements A and B prepared using a p-type Si substrate, similarly to Fig. 18. As shown in Fig. 19, both EL light-emitting elements A and B emitted light, and it was observed with the naked eye that EL light-emitting element A emitted white light, and EL light-emitting element B emitted red light. Therefore, it was found that the niobium oxide nanoparticles according to one embodiment of the present invention may have different emission colors even when subjected to the same preparation method and the same measurement method.
[0140] [Test 10. Measurement of the luminescence characteristics of EL light-emitting devices] A probe electrode was brought into contact with the ITO layer of an EL light-emitting device prepared using a p-type substrate by the preparation method described in [Test 9. Preparation of EL light-emitting device] in the same manner as in Test 9, and a voltage was applied to the device using the same power source as in Test 9 until light emission from the EL light-emitting device was visually confirmed. Next, the emission spectrum was measured using a spectrometer SP2358 (manufactured by Princeton Instruments) and a photodetector PI-MAX4 (manufactured by Princeton Instruments). In order to confirm reproducibility, the measurement was performed using two different EL light-emitting devices prepared by the preparation method described above.
[0141] The results of measuring the emission spectra of the two different EL light-emitting devices are shown in Figures 20 and 21. In Figures 20 and 21, the broken lines are blank spaces caused by the device, and no new emission peaks are present, with the emission spectra of the blank spaces rising smoothly.
[0142] It was found from Fig. 20 that the EL device according to one embodiment of the present invention emits light that appears white to the naked eye, has an emission peak at a wavelength of about 650 nm, and emits light over the entire visible light range. On the other hand, as shown in Fig. 21, even among EL device elements obtained by the same preparation method and subjected to the same measurement method, there were some EL device elements that emitted light that had an emission peak in the infrared light range at a wavelength of about 810 nm and appeared red or orange to the naked eye.
[0143] The emission spectra of the EL light-emitting elements A and B were also measured in the same manner as for the two EL light-emitting elements. The measurement result of the emission spectrum of the EL light-emitting element A is shown in FIG. 22, and the measurement result of the emission spectrum of the EL light-emitting element B is shown in FIG. 23. As shown in FIG. 22, the EL light-emitting element A was found to have an emission peak at a wavelength of about 650 nm and to have emission over the entire visible light range, similar to the EL light-emitting element shown in FIG. 20 that emitted light that appeared white to the naked eye. Also, as shown in FIG. 23, the EL light-emitting element B showed a spectrum with an emission peak in the infrared light range at a wavelength of about 810 nm, similar to the EL light-emitting element shown in FIG. 21 that emitted light that appeared red or orange to the naked eye.
[0144] In addition, for two EL light-emitting devices prepared using a p-type substrate by the preparation method described in [Test 9. Preparation of EL light-emitting devices], a probe electrode was brought into contact with the ITO layer in the same manner as in Test 9, and the current-voltage characteristics (IV characteristics) were measured using the same power supply as in Test 9.
[0145] The measurement results of the IV characteristics of the EL light-emitting elements are shown in Figures 24 and 25. One of the two EL light-emitting elements exhibited diode-like rectification characteristics of current with respect to the applied voltage, as shown in Figure 24. On the other hand, the other EL light-emitting element did not exhibit the rectification characteristics of the one EL light-emitting element, and instead exhibited ohmic characteristics, although they were non-uniform with respect to the applied voltage, as shown in Figure 25.
[0146] Thus, both of the two EL light-emitting devices emitted light, as shown in Figures 24 and 25. However, no correlation was found between the emission color and the rectification and ohmicity of the IV characteristics. In addition, the EL light-emitting device whose IV characteristics showed ohmicity emitted light regardless of whether the applied voltage was positive or negative. Therefore, it was found that the niobium oxide nanoparticles according to one embodiment of the present invention can emit light of various wavelengths by themselves. [Industrial Applicability]
[0147] INDUSTRIAL APPLICABILITY The present invention is capable of producing niobium oxide nanoparticles of a single nano size, and therefore can be suitably used as various light-emitting materials.
Claims
1. The following steps (A) to (C): (A) dissolving a niobium complex in a reducing agent as a solvent to produce a precursor solution; (B) adding a halogen-containing additive to the precursor solution; (C) heating the precursor solution containing the additive at 140° C. or higher; the reducing agent is one or more selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-vinylformamide, N-methylformamide, and N-methyl-2-pyrrolidone; The additive is at least one selected from the group consisting of trimethylsilyl chloride, trimethylsilyl bromide, hydrochloric acid, dimethyldichlorosilane, and butyldimethylchlorosilane; A method for producing niobium oxide nanoparticles.
2. 2. The method according to claim 1, wherein the niobium complex is one or more complexes selected from the group consisting of niobium oxalate, niobium acetate, niobium acetylacetonate, niobium pentachloride, niobium pentabromide, niobium pentaethoxide, and salts thereof.
3. The method according to claim 1 or 2, wherein the concentration of the niobium complex in the precursor solution is 0.01 M or more.
4. The method according to any one of claims 1 to 3, wherein in the step (B), a molar ratio of niobium in the precursor solution to the halogen contained in the additive is greater than 1:1 and is 1:10 or less.
5. Infrared spectroscopy revealed that the peak at 1600-1750 cm -1 Niobium oxide nanoparticles in which a peak showing C═O stretching vibration is detected, halogen atoms are confirmed by energy dispersive X-ray analysis, and the average particle size measured by dynamic light scattering is less than 10 nm.
6. The niobium oxide nanoparticles according to claim 5, characterized in that the halogen atom is fluorine, chlorine, bromine, or iodine.
7. The niobium oxide nanoparticles according to claim 5 or 6, wherein the niobium molecule is protected by a molecule used as a reducing agent.
8. A luminescent material comprising the niobium oxide nanoparticles according to any one of claims 5 to 7.
9. The light emitting material of claim 8 , wherein the light emitting material is an electroluminescent material.
10. A light-emitting device comprising the light-emitting material according to claim 8 or 9.
11. The light emitting device of claim 10, wherein the light emitting device is an EL light emitting device.
Citation Information
Patent Citations
Metal oxide nanoparticle, method for producing the same, light emitting element assembly, and optical material
JP2007204354A
Dye sensitized solar cell
JP2014146534A
Composite material
JP2017224815A
Semiconductor film, method for producing same, photoelectric conversion element, solid-state imaging element and electronic device
WO2018016213A1